Optimization of Critical Factors for In Vitro Vegetative Growth of Pleurotus cornucopiae to Improve Branched Oyster Mushroom Production - Arunesh Kumar; R. S. Jarial; Kumud Jarial; Savita Jandaik; Meenu Gupta; Chidembra Bhardwaj; Satish Kumar Sharma; Ankita; Surender Kumar (International Journal of Economic Plants)
The present investigation was carried out during (January–April) 2025 at Mushroom Research Laboratory, Department of Plant Pathology, College of Horticulture and Forestry, Neri, Hamirpur (HP) in which effect of different cultural parameters on vegetative growth of P. cornucopiae was evaluated. Mushroom, an edible fungus, grows on moist surfaces such as wood or other organic matter including natural or semi-synthetic compost and consume globally due to their high nutritious vegetarian delicacy. The first crucial step in the successful generation of spawn was the preservation and restoration of a pure mycelium culture of exceptional quality. The fungus P. cornucopiae, branched oyster mushroom was widely used due to its nutritional and medicinal properties. Its cultivation was rather new in Indian conditions and much work has not yet been done. The solid and liquid media including potato dextrose, malt extract, oat meal, Asthana and Hawker’s and Czapek’s dox were evaluated in the present study for P. cornucopiae growth in which maximum diametric growth on potato dextrose agar and minimum on Asthana and Hawker’s agar were recorded. Similarly, maximum biomass was observed in potato dextrose broth and minimum in Asthana and Hawker’s broth. The growth was maximum under neutral and minimum under acidic condition, which ranged from sparse, fluffy to thick strand, and optimum at 25 °C and pH 7. It will require to validate these findings through comparative studies on different mushroom varieties.